In silico identification of the anticataract target of βB2-crystallin from Phaseolus vulgaris: a new insight into cataract treatment - Sunday Amos Onikanni; Sunday Amos Onikanni; Adewale Oluwaseun Fadaka; Tran Nhat Phong Dao; Tran Nhat Phong Dao; Valens Munyembaraga; Valens Munyembaraga; Vincent Nyau; Nicole Remaliah Samantha Sibuyi; Morenike Grace Ajayi; Nguyen Thi Ai Nhung; Emmanuel Ejiofor; et al. (Frontiers in Chemistry)
IntroductionSevere protein clumping in the lens can block light and lead to vision issues in cataract patients. Recent studies have linked β-crystallins, which are key proteins in the lens, to the development of cataracts. Specifically, the S175G/H181Q mutation in the βB2-crystallin gene plays a major role in cataract formation.MethodsTo understand how this mutation can be activated, we utilized computational methods to predict activators from Phaseolus vulgaris. The Schrödinger platform was employed to screen bioactive compounds and simulate molecular interactions in order to analyze binding and structural changes.ResultsOur results indicated that these phytochemicals are stable near S175G/H181Q.DiscussionThese findings suggest novel approaches that could potentially be developed into effective anticataract medications through further refinement and additional testing, ultimately resulting in the creation of more potent agents for cataract treatment.